22. Using Birleson Depression Self-Rating Scale to Measure Depressive Symptoms among Urban Adolescents in Hanoi, Vietnam - Vinh, Ngo Anh; Ut, Nguyen Thi (Tạp chí Nghiên cứu Y học, 2024)
This study was conducted to assess the prevalence of depressive symptoms among adolescents using the Birleson Depression Self-Rating Scale (DSRS) and to explore how demographic factors such as gender, grade level, and academic performance influence these symptoms. This is a cross-sectional study involving 996 students from two secondary schools in Hanoi, Vietnam. Participants completed the DSRS, and data were analyzedto calculate the prevalence of depressive symptoms. Associations between depressive symptoms and demographic factors were examined using odds ratios and regression analysis. The overall prevalence of depressive symptoms was 11%. Males reported significantly higher depressive symptoms compared to females (OR=0.52, p < 0.01). Depressive symptoms varied by grade but did not show a significant gradient, with seventh and sixth graders showing slightly lower symptom scores compared to eighth graders. Academic performance was related to depressive symptoms, with students performing poorly showing higher rates of depression, though this was not statistically significant across all levels. The study confirms the utility of the DSRS in detecting depressive symptoms in adolescents and highlights significant gender and academic performance disparities in the prevalence of these symptoms. The findings suggest the need for targeted mental health interventions and school support systems to address the identified risk factors.